Teacher Pedagogical Competence in Using Technology for Teaching English at A State Vocational High School in Mataram - Amir Linda Tyas Hartatik; Muhammad Amin; Kurniawan Apgrianto (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2022)
In the current era of globalization, a teacher must have pedagogical competence in utilizing technology. The development of the use of technology in the world of education is currently non-negotiable because it has been integrated with the development of every activity of life, including in the world of education. This study aimed to know how the pedagogical competence in using technology in teaching English at a state vocational high school in Mataram. This type of research is a descriptive qualitative method. The subjects of this study were three English teachers at a state vocational high school in Mataram. Data were collected by observation, interview, and documentation. Then, the data analysis procedures in this study include data reduction, data display, and drawing conclusions. The results showed that the pedagogical competence of teachers in using technology as a learning medium in teaching English at a state vocational high school in Mataram was very good, the teachers can apply ICT-based learning media and are skilled in utilizing ICT facilities to develop the material into interesting learning media. So, that the learning process feels fun, creative, innovative, and gives a new spirit in doing the learning. Learning by utilizing technology as a learning medium is a solution for teachers and students in creating the expected classroom atmosphere.